Argentine Ministers and Ministries: A Prosopographic Analysis of the Cabinet (1854-2011) - Giorgi, Guido Ignacio (2014)
This article is framed within sociological debates on political elites and seeks to account for the correlation between certain socio-professional profiles prevalent among Argentine ministers between 1854 and 2011 and the portfolios they held. Our working hypothesis is that ministerial nominations depend on broader sociological logics, including those analyzed here. Our cartographic approach aims to identify patterns shared by all cabinets in this period in order to contribute to the understanding of specific cases through a comprehension of general characteristics.